2018
DOI: 10.1007/s00216-018-1499-3
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical flow field-flow fractionation for improved characterization of human plasma lipoproteins

Abstract: High and low-density lipoproteins (HDL and LDL) are attractive targets for biomarker discovery. However, ultracentrifugation (UC), the current methodology of choice for isolating HDL and LDL is tedious, requires large sample volume, results in sample loss, and does not readily provide information on particle size. In this work, human plasma HDL and LDL are separated and collected using semi-preparative asymmetrical flow field-flow fractionation (SPAF4) and UC. The SP-AF4 and UC separation conditions, sample th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 41 publications
(47 reference statements)
1
11
0
Order By: Relevance
“…Still, most of smaller particles were not included in particle radius calculations in our study, as they co-eluted with other contaminants that absorb UV light. Our 31 and other studies namely showed that UV detector at 280 nm measures proteins 64 and lipoproteins 65 in the sample. To exclude the effect of impurities on EV quantification, we effectively included in the AF4-UV-MALS analysis only particles with 2* R geom larger than ≥ 120 nm.…”
Section: Discussionsupporting
confidence: 63%
“…Still, most of smaller particles were not included in particle radius calculations in our study, as they co-eluted with other contaminants that absorb UV light. Our 31 and other studies namely showed that UV detector at 280 nm measures proteins 64 and lipoproteins 65 in the sample. To exclude the effect of impurities on EV quantification, we effectively included in the AF4-UV-MALS analysis only particles with 2* R geom larger than ≥ 120 nm.…”
Section: Discussionsupporting
confidence: 63%
“…6, AF4 can be particularly useful in these situations, being an ideal technique when it comes to fractionating complex mixtures. Numerous methods have been developed for the analysis of complete plasma or serum and can be easily applied to study drug transfer to plasma proteins [163][164][165][166][167]. As a common rule, plasma samples are fractionated in physiological buffers to preserve the structure and properties of the proteins.…”
Section: Drug Transfer To Plasma Proteinsmentioning
confidence: 99%
“…AF4 presents several limitations, though: peak broadening is more accentuated than chromatography, and baseline separation is often unfeasible. Although deconvolution methods have been developed to improve peak resolution [170], more often than not it may not be possible to identify exactly the protein to which the drug is transferred: consider, for example, that albumin and high-density lipoproteins are both acceptors of lipophilic drugs, and being of similar size their peaks have a high chance of overlapping [164,167]. Once acknowledged its limitations, AF4 is a powerful tool in the study of drug release to serum proteins.…”
Section: Drug Transfer To Plasma Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most proteomic studies of plasma lipoproteins rely on ultracentrifugation techniques that are time consuming (e.g., 5.7 h), demand large sample volumes (e.g., 640 μL), and damage the integrity and loss of apolipoprotein content of lipoproteins due to its high shear force [ 9 ] . Recently, there have been advancement of methods for lipoprotein fractionation such as flow field‐flow fractionation [ 10 ] . HDL subclass proteomics analysis also has revealed dynamic protein change during HDL maturation [ 11 ] .…”
Section: Figurementioning
confidence: 99%